Optimal Diabetic Therapy Selection under Uncertainty: A Sinusoidal Pythagorean Fuzzy MOORA and TOPSIS Approach - Vishalakshi Kuppusamy; Prasantha Dhandapani; Kalarani Murugesan; Kavitha Arumugam; Hasan Panigoro; Rebecca Nalule (Jambura Journal of Biomathematics (JJBM), 2026)
Sinusoidal waves are fundamental to the analysis and synthesis of signals in engineering, physics, and applied sciences. Their periodic nature and mathematical simplicity make them essential in modelling oscillations, communication signals, and even artificial intelligence systems where signal patterns matter. In this paper, we introduce a new class of sinusoidal Pythagorean fuzzy set. We define a sinusoidal Pythagorean fuzzy average aggregation operator and discuss its properties. This operator is then applied in decision-making problems using sinusoidal Pythagorean fuzzy CRITIC method, sinusoidal Pythagorean fuzzy MOORA method, and sinusoidal Pythagorean fuzzy TOPSIS method for optimal diabetic therapy selection under uncertain clinical judgements.